Reducing Ergonomic Risk and Musculoskeletal Complaints through Participatory Ergonomics in an Informal MSME Food-Processing Enterprise: A Quasi-Experimental Case Study - Nana Rahdiana; Afif Hakim; Suryadi Suryadi; Bambang Suhardi; Jafri Mohd Rohani; Falahal Majid; Nindya Fatharani Shafa (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Informal micro and small-scale enterprises in developing countries frequently operate under suboptimal occupational safety and health conditions, exposing workers to significant ergonomic risks and musculoskeletal disorders (MSDs). This study examined whether a participatory ergonomics (PE) intervention was associated with reductions in ergonomic risk and musculoskeletal complaints in small-scale milkfish processing enterprises in Indonesia. Methods: A quasi-experimental, one-group, pretest-posttest design was implemented over three months, involving 12 workers. Ergonomic risk was assessed using the Rapid Entire Body Assessment (REBA), musculoskeletal complaints were evaluated using the Nordic Musculoskeletal Questionnaire (NMQ), and workplace hazards were identified using the ILO-PATRIS checklist with Delphi-based prioritization. Results: Following the intervention, the mean REBA score decreased from 9.25 (high risk) to 4.75 (moderate-low risk), representing a 48.6% reduction. The prevalence of lower back complaints declined from 91% to 46%, shoulder complaints from 78% to 35%, and wrist complaints from 63% to 28% after the intervention. Perceived work comfort increased by 46.4 percentage points. These changes suggest meaningful ergonomic improvements associated with participatory interventions and low-cost workstation modifications. Conclusion: The findings indicate that participatory ergonomics may offer a feasible and contextually adaptable strategy for mitigating ergonomic risks and promoting worker well-being in informal MSME food-processing environments.